Obstacles to the use of e-learning from the point of view teacher of the history In misan province - Salman Hassan, Suaad (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to know the obstacles of e-learning from the point of view of the history teacher in Misan province, since the research was limited to the faculty of education and the faculty of dentistry, as they are the newest faculties in Misan University and they also represented the research samples, which reached 100 samples consisting of 50 human specialties and 50 scientific specialties for the academic year 2018-2019. The researcher prepared a questionnaire consisting of 30 clauses, and everyone had five alternatives (strongly agree , agree, neither, disagree, strongly disagree). Then the data was processed statistically using the Pearson and Spearman correlation coefficient. It was concluded that e-learning is an integrated educational system in the delivery of science and knowledge to the learners without time and place restrictions. The researcher recommends the faculty members take training courses to help them in teaching and spread the electronic culture between the society members to achieve the most interaction with this type of education. The researcher suggest make similar studies in other faculties in Misan university , and make experimental study to the effectiveness of learning in some variables such as achievement and thinking